Comparison of ante-versus retrograde access for the endovascular treatment of long and calcified, de novo femoropopliteal occlusive lesions - Giusca, Sorin; Lichtenberg, Micheal; Hagstotz, Saskia; Eisenbach, Christoph; Katus, Hugo; Erbel, Christian; Korosoglou, Grigorios (Heart and vessels, 2020)
To compare antegrade versus retrograde recanalization, in terms of procedural time, radiation and contrast agent exposure, number and total length of implanted stents and procedural complications, in long and calcified, de novo femoropopliteal occlusions. We performed retrospective matching of prospectively acquired data by lesion length, occlusion length and lesion calcification by the peripheral arterial calcium scoring system (PACSS) score in patients who were referred for endovascular treatment due to symptomatic peripheral artery disease (PAD). Forty-two consecutive patients with antegrade and 23 patients with retrograde after failed antegrade recanalization were identified (mean lesion length = 32.1 ± 6.9 cm; mean occlusion length = 24.6 ± 7.7 cm; PACSS score = 3.25 ± 0.91). 23% of the patients had intermittent claudication, whereas 77% exhibited critical limb ischemia (CLI). Patients who underwent retrograde versus antegrade recanalization required a significantly lower number of stents (0.9 ± 1.0 versus 1.8 ± 1.4, p = 0.01) and a lower total stent length (6.8 ± 8.5 cm versus 11.7 ± 9.9 cm, p < 0.05) in the interest of more extensive coverage of the lesions using drug coated balloons (DCB) (28.5 ± 12.0 cm versus 18.2 ± 16.0 cm, p = 0.01). No re-entry device was required with the retrograde versus 9 of 42 (21%) with the antegrade recanalization group (p = 0.02). The rate of complications due to retrograde puncture was low (one patient with hematoma and one with distal pseudoaneurysm, both managed conservatively). In long and calcified femoropopliteal occlusions, the retrograde approach is associated with a lower number of re-entry devices and stents and with more extensive lesion coverage with DCB, in the interest of costs and possibly long-term patency.